Polarization: a diagnostic tool for protoplanetary disks - Bacciotti, Francesca (Il Colle di Galileo, 2021)
The rotating disk of gas and dust observed around young stars is the birthplace of planets. The study of its properties is fundamental to understand the formation and evolution of nascent worlds. Polarimetric data obtained with the Atacama Large Millimeter/Submillimeter Array (ALMA) are a new powerful tool to investigate the properties of the dust and magnetic structure in these systems.